Transforming the CIP Data Block: Assessing User Needs to Re-envision a Venerable Library Icon. Issue 7 (17th November 2017) - Debus-López, Karl; McCroskey, Marilyn; Reynolds, Regina Romano; Saccucci, Caroline; Williams, Camilla; Zwierski, Michele
ABSTRACT: Between 2013 and 2015, the Library of Congress and experts from school, public, and academic library communities revised the 42-year-old Cataloging in Publication (CIP) data block (back-of-title-page cataloging data). This article describes the assessments, including development and analysis of two surveys, used in this data-driven process. The revised data block replaces the catalog card layout with a labeled layout that identifies components within the block, merges print and electronic information, and provides additional descriptive and subject access points. A 2017 follow-up assessment confirmed the project's success in meeting the needs of its principal users, those in school and public libraries.